If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -42m + -15 = 57 Reorder the terms: -15 + -42m = 57 Solving -15 + -42m = 57 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + -42m = 57 + 15 Combine like terms: -15 + 15 = 0 0 + -42m = 57 + 15 -42m = 57 + 15 Combine like terms: 57 + 15 = 72 -42m = 72 Divide each side by '-42'. m = -1.714285714 Simplifying m = -1.714285714
| 2(2y+7)=18 | | 3(2l+9)=93 | | (2x/3y)x(9y/4x^2) | | tan=1.7 | | 2g+2u=q | | 11-2x+4=8+4x | | (13/52)*(12/52) | | X/-6=-9 | | 3(12+6r)= | | 6(3r+5)+1= | | 25x^6-49b^2=0 | | x*x*x=-27 | | -x+18=4 | | -2(x+1)=-22 | | (5w-3y+4)(7w+1)=0 | | 7x+33=9x+7 | | 8p-16=4p+32 | | 5+109875432=+13689765 | | 8x+4=3x+6 | | 5*+10987655321= | | 3x+5=27x-1 | | 1-3(2m-7)=4 | | -5(x-1)=3x+1-4x | | 32+90+x=180 | | 5/9(-13-32) | | 2x^3+4x^2+4x=-5 | | 4x-32+5x+45=36 | | 2-5m+7=8+2m | | 2x^3+4x^2+4x+5=0 | | 4x-2x=4x-2 | | x^6=14 | | y^2-2x^2=-32 |